Neotropical orchid eco-tourism: educational experience of an orchid neophyte at the Bosque de Paz Biological Preserve, Central Volcanic Range, Costa Rica - Kirby, Stephen (Lankesteriana: International Journal on Orchidology, 2016)
The purpose of this presentation is to describe the efforts of the owners of the Preserve to attract the interest of orchid profes- sionals and amateur enthusiasts to this mountain haven and to consider more ways in which orchid eco-tourism might be encouraged to grow to the ben- efit of Costa Rica, orchid science and the conserva- tion of orchid habitat.